Investigating the mechanisms of resveratrol in the treatment of gouty arthritis through the integration of network pharmacology and metabolics - Xu, Xiaomin; Yu, Donghua; Wang, Yu; Jiang, Xin; Lu, Fang; Liu, Shumin (Frontiers in Endocrinology, 2024)
Objective: This study integrates network pharmacology and metabolomics techniques to explore the potential regulatory mechanisms of Res on gouty arthritis (GA). Methods: Network pharmacology was used to predict the mechanism of Res in regulating GA, and methods such as HE staining, ELISA, immunohistochemistry, Real-time PCR, Western blot, and molecular docking were used to verify the role of NF-κB, MAPK, and JAK/STAT inflammatory signaling pathways in the MSU-induced GA rat model. In addition, non-targeted metabolomics techniques were combined to further investigate the mechanism of Res in treating GA. Results: The results of network pharmacology showed that Res may exert its therapeutic effects through the NF-κB signaling pathway. Animal experiments demonstrated that in the MSU-induced GA rat model, pathological damage, serum biochemical indicators, and levels of inflammatory factors were significantly increased, and the NF-κB signaling pathway was activated. The intervention of Res significantly reduced pathological damage, serum biochemical indicators, levels of inflammatory factors, and the activation of NF-κB, MAPK, and JAK/STAT signaling pathways in the model rats. Metabolomics results showed that Res could improve the metabolic trajectory deviations in serum and joint fluid of GA model rats. Through related metabolic pathway analysis, the most affected metabolic pathways were found to be Sphingolipid metabolism, Glycerophospholipid metabolism, Phenylalanine, tyrosine and tryptophan biosynthesis, Pantothenate and CoA, Citrate cycle (TCA cycle), and Arachidonic acid metabolism. Conclusion: Resveratrol can regulate the biosynthetic pathways of arachidonic acid, phenylalanine, tyrosine, and tryptophan, pantothenic acid and CoA biosynthesis pathways, TCA cycle, and other metabolic pathways, thereby regulating the NF-κB, MAPK, and JAK/STAT3 signaling pathways, and inhibiting the acute inflammatory response during GA attacks, showing characteristics of multi-pathway and multi-target action.